ANALISIS KARAKTERISTIK CAMPURAN ASPAL DITINJAU DARI ASPEK PROPERTIES MARSHALL - M Zain Triputra; Agung Prapsetyo; Kiki Lestari (PPM Sdirjianbang Akademi Militer, 2023)
In infrastructure development today, the transport facilities is the main thing, especially land transport most in demand by the users of transport. Therefore, it is necessary to increase the quality of the pavement needs both in terms of strength, safety and comfort. This study is to analyze how the characteristics of asphalt mixtures with Marshall method. And the result showed that the most optimum usage levels of the mixture is bitumen content of 5.9% with the addition of a latex content of 5%. Optimum bitumen content to be used as an asphalt concrete by using AC 60/70 and aggregate Bantak is asphalt content of 6.5%. The test results on the Marshall characteristics Optimum Asphalt Content 6.5%. Density value of 2.33 g / cc. Value VMA (Void in Mineral Aggregate) amounted to 13.92%. c. Value VFB (Void Filled Bitumen) amounted to 60.10%. Value VIM (Void In Mix) by 5.2%. Marshall Stability value of 1156.44 kg. Value Flow (melting) of 3.07 mm. Marshall Quotient obtained was 377.28 kg / mm.